Clinical Effectiveness of Anterior Repositioning Splints in Treating Temporomandibular Joint Disc Displacement with Reduction: A Systematic Review and Meta-Analysis - Tayyaba Rafiq; Aqsa Sajji; Iqra Bibi; Mahvish Jabeen; Misbah Noreen; Sajid Ali Majeedano; Ehsan Ul Haq (Pakistan Journal of Medicine and Dentistry, 2025)
Background: The prevalent condition known as Temporomandibular joint disc displacement with reduction (DDwR) results in pain, together with joint sounds and problems related to the jaw structure. ARS treatment for DDwR was studied in this systematic review and meta-analysis to determine its effect on joint symptoms and pain intensity.